Identidad cultural y desarrollo del turismo en el distrito de San Juan Bautista, Maynas 2023 - Vasquez Morey, Shayany Maylayne (2025)
The objective of this research was to analyze the relationship between cultural identity and the development of tourism in the San Juan Bautista district, Maynas 2023. To this end, a basic study, with a correlational descriptive level, was carried out, in which 383 local residents participated. The survey and the questionnaire were used as techniques and instruments. Descriptive results indicated that 28% of respondents perceived cultural identity as regular, as they only occasionally identified with local customs and traditions. Likewise, tourism development was rated as fair by a similar percentage, showing indifference to tax collection and discordance with cultural identity, but apathy towards environmental protection. Regarding the inferential results, a statistical significance was found with a value of Sig. = 0.000 < 0.05 and a Spearman's correlation coefficient (Rho) of 0.833, which suggests a very strong positive correlation between cultural identity and tourism development in the district.